(untitled) (Research, Society and Development, 2021)
The food industry is looking for strategies to prevent microbial growth in order to ensure food safety and shelf life. However, the use of synthetic preservatives, such as nitrate and nitrite in meat products, entails risks to human health. An alternative is the utilization of essential oils, widely known for their antimicrobial properties. This work aimed the antimicrobial potential of a bioactive coating based on chitosan incorporated with clove essential oil in in hamburger-like meat product. Through the analysis of antimicrobial activity by diffusion in agar and broth, there was an action against Gram-positive and Gram-negative bacteria. Regarding Staphylococcus aureus and Escherichia coli, the minimum inhibitory concentration (MIC) was 3.74 mg/mL and the minimum bactericidal concentration (MBC) was 374.33 mg/mL for both. In the micro atmospheric diffusion test, CEO reduced by up to 70 and 76% of the E. coli and S. aureus bacteria development, respectively. CEO was applied as an active component in chitosan-based coatings in hamburger-like meat, in which it was able to promote the control of microbial proliferation of Total Coliforms, Coliforms at 45 ⁰C and Coagulase-Positive Staphylococcus throughout 7 days of storage under refrigeration. It is concluded that the bioactive coating based on chitosan incorporated with clove essential oil promotes microbiological control in hamburger-like meat product.